PENGARUH PENGGUNAAN LKS BERORIENTASI STM DENGAN MENGINTEGRASIKAN NILAI KARAKTER TERHADAP HASIL BELAJAR FISIKA SISWA KELAS XI SMA NEGERI 1 KOTA SOLOK - Deyesa J. Delin (PILLAR OF PHYSICS EDUCATION, 2014)
This research based of the a problem in teaching and learning proses with not apparent invisibility of interest in students to learn science. Based on these problems, resulting in student's learning outcomes is not maximized. By those reasons student worksheets oriented Science Technology Society (STM) is one of the learning materials that are considered effective to overcome these problems.Type of research is quasi- experimental research design. The population of this research is class XI of science program SMAN 1 Solok enrolled in the academic year 2013/2014. Sampling was done by purposive sampling technique. The research instrument is the final test for cognitive learning outcomes, observation format for affective learning outcomes, rubric scoring for the psychomotor domain of learning outcomes.  Data obtained from the research were analyzed using  tes t to cognitive test and two average similarity to the affective and psychomotor domains. Based on the research that has been done, it can be concluded that there is a significant influence of using student worksheets  oriented STM by integrating the value of character the ability of the student in the cognitive, affective , and psychomotor domains at the 95 % significance level